Members Travel And Tours Sdn. Bhd. / Liza Salleh ... [et al.] - Salleh, Liza; Ahmad Sabri, Noor Azrina; Kuat Khan, Norihan; Abdullah, Maizatu Azira; Sulaiman, Syairah (2002)
Our business is operating as a company under private limited company which have five shareholders. The all five shareholders are also the company managers such as general manager, administration manager, marketing manager, operation manager and financial manager. It is gazette under private limited company because it is one of criteria to get license from Kementerian Kebudayaan, Kesenian dan pelancongan Malaysia.